A panel of diverse Pseudomonas aeruginosa clinical isolates for research and development. Issue 4 (10th December 2021) - Lebreton, Francois; Snesrud, Erik; Hall, Lindsey; Mills, Emma; Galac, Madeline; Stam, Jason; Ong, Ana; Maybank, Rosslyn; Kwak, Yoon I; Johnson, Sheila; Julius, Michael; Ly, Melissa; et al.
Abstract: Objectives: Pseudomonas aeruginosa is a leading cause of community- and hospital-acquired infections. Successful treatment is hampered by its remarkable ability to rapidly develop resistance to antimicrobial agents, primarily through mutation. In response, WHO listed carbapenem-resistant P. aeruginosa as a Priority 1 (Critical) pathogen for research and development of new treatments. A key resource in developing effective countermeasures is access to diverse and clinically relevant strains for testing. Herein we describe a panel of 100 diverse P. aeruginosa strains to support this endeavour. Methods: WGS was performed on 3785 P. aeruginosa isolates in our repository. Isolates were cultured from clinical samples collected from healthcare facilities around the world between 2003 and 2017. Core-genome MLST and high-resolution SNP-based phylogenetic analyses were used to select a panel of 100 strains that captured the genetic diversity of this collection. Antibiotic susceptibility testing was also performed using 14 clinically relevant antibiotics. Results: This 100-strain diversity panel contained representative strains from 91 different STs, including genetically distinct strains from major epidemic clones ST-111, ST-235, ST-244 and ST-253. Seventy-one distinct antibiotic susceptibility profiles were identified ranging from pan-susceptible to pan-resistant. Known resistance alleles as well as the most prevalent mutations underlying the antibiotic susceptibilities were characterized for all isolates. Conclusions: This panel provides a diverse and comprehensive set of P. aeruginosa strains for use in developing solutions to antibiotic resistance. The isolates and available metadata, including genome sequences, are available to industry, academia, federal and other laboratories at no additional cost.